Digital transformation of the government of Ukraine, open data and electronic services - Bondar, Hanna (Public Administration and Regional Development, 2021)
The article is devoted to the analysis of the peculiarities of the activity and state of reforms in Ukraine in the direction of digitalization of services, their accessibility to citizens, development of e-government, ensuring transparency of open data. Legislative and regulatory support for the functioning and development of e-government in the direction of digital transformation of the government and the implementation of international obligations of Ukraine is analyzed. The research data of European and international institutions on the development of e-government, open data and e-services in the world and in Ukraine are analyzed and systematized. The peculiarities of the realization of e-government opportunities in Ukraine during the fight against the pandemic (COVID-19) are revealed. In particular, this applies to the provision of electronic services, and the transfer of most administrative services online. The problems influencing the development of digital government of Ukraine are analyzed. It is established that there is currently an insufficient development of ICT in Ukraine, there are limited resources, there are problems related to digital inclusion, data confidentiality and cybersecurity. We conclude that the process of creating and developing national portals to automate administrative tasks, increase the availability of public services, and promote transparency and accountability of the public sector is under way. Also, the development of ICT, overcoming digital inequality in the country - is an important prerequisite for Ukraine's exit from the socio-economic crisis, and new challenges are forcing the government to develop its own e-government strategy focused on data. The digital transformation of government is also logically linked to the transformation of governance and value, worldview changes to develop a national development strategy.